Bobby and Jackie [compact disc, unabridged] : a love story - Heymann, C. David (Clemens David), 1945-2012 (Tantor Audio, 2009)
From the New York Times bestselling author of American Legacy; RFK; and A Woman Named Jackie comes an in-depth look at the much talked-about, but never fully revealed, relationship between Jackie Kennedy and Robert F. Kennedy.